MEMBANGUN KINERJA PEMASARAN BERBASIS INOVASI PRODUK DAN KEUNGGULAN BERSAING (STUDI EMPIRIS PADA KERAJINAN GITAR DI KABUPATEN SUKOHARJO) - Setyani Sri Haryanti; Linda Nursusila (STIE AUB Surakarta, 2016)
This research target are to know and give the empirical evidence, effort to do the study in more circumstantial hit how to develop; build a model Develop; Build The Marketing Performance Base on the Innovation of Product and Excellence Compete the ( Empirical Study at Crafting of Guitar in Regency Sukoharjo. Data used primary data taken with the questionnaire given to craftmen guitar in Countryside of Mancasan of Subdistrict of Baki of Regency Sukoharjo, as many as 110 craftmen as sampel. Technique appliance analyse the data in this research will use the Structural model of Equation Modelling ( SEM) by using program of equation of structural Partial Least Square ( PLS) 3. Result of test of Assessment instrument Model The Measurement (Outer Model) with the Assessment of convergent validity own the loading factor to its contruct which signifikan statistically, Assessment of Descriminant Validity fulfill the criterion, Assessment of Composite Reliability all item explaining construct at this research have the reliabilitas which high enough. Structural Model Assessment ( Inner Model) visible assess the R Square of each; every variable endogen. By R-Square is Marketing Performance equal to 0,527 inferential hence that Environmental Uncertainty variable contribution, Intensity Litbang, Orient The [Cutomer/ Client], Orient The Product, Innovate the Product and Excellence Compete to Marketing Performance equal to 52,7% and the rest influenced by other;dissimilar factor outside accurate. Hypothesis examination with the boundary to refuse and accept the hypothesis raised by ± 1,65, where if value t be at to span the value - 1,65 and 1,65 hence all hypothesis is accepted because value t reside in above 1,65 Keyword : Environmental Uncertainty, Intensity Litbang, Orient The Cutomer, Orient The Product, Innovate the Product, The Excellence Compete ansd Marketing Performance.